Use of Digital Resources by High School Math Teachers: An Exploratory Study: Uso de recursos digitales por profesores de matemáticas en secundaria: un estudio exploratorio - Padilla Ordoñes, José Lucas (2021)
The results of a research on the use of digital resources by Mexican secondary mathematics teachers are presented. A sample of 81 teachers from 24 secondary schools was selected to answer a questionnaire and interviews with the purpose to explore ways of use and resources selection, the interactions that teachers establish with them, as well as institutional factors and beliefs that determine its use. The results show a limited professional training of the teachers in the use of digital resources, attributable to institutional conditions, but also to beliefs and attitudes of the teachers towards the technology. A low level of integration of the digital resources to the teaching process was observed, mainly with activities focused on the transmission of contents.